Social capital assessments in higher education: a systematic literature review - Adrian Nat Gentry; Julie P. Martin; Kerrie A. Douglas (Frontiers in Education)
Social capital theory is a valuable theoretical framework in the field of higher education—as it has been used to examine differences in important educational outcomes based on students’ social network and the resources embedded in that network. Despite multiple well-established methods proposed by seminal researchers, there is limited synthesis of how to assess social capital, perpetuating inconsistent findings and evidence for educational interventions. The aim of the study is to evaluate quantitative social capital assessments, based on survey design and operationalized measures, and recommend methods, operationalized measures and assessment instruments for social capital. Using seven educational databases and Web of Science, we reviewed 93 English language, quantitative studies from peer-reviewed journals, published from 1980 to 2022; to be included, studies had to measure the social capital of students entering and currently in undergraduate studies. Results from the 93 articles revealed that generators (18 papers), social network analysis (5 papers), and standard Likert measures (80 papers) were commonly used to assess social capital. Standard Likert measures, while most common, were rarely aligned with social capital theory, reducing the validity of the measures. Results also showed that operationalizations of social capital were heavily rooted in social network theory, where social capital is accessed through social networks (86 papers) and actions from alters (65 papers) in the students’ network. However, direct measures of social capital—that is, network characteristics, access to supports, and seminal definitions of trust and community—were less common. This study provides important consensus and recommendations for researchers to select assessment instruments appropriate for their study and rooted in principles of assessment validity. We recommend researchers select survey methods (e.g., social capital generators) and operationalizations (e.g., actions from alters) that are well aligned with social capital theory. Assessment instruments designed using strong theoretical frameworks, such as Lin’s network theory of social capital, add to the validity of the researchers’ instrument design, use and interpretation of the students’ social capital scores.